Comparing Case Study and Ethnography as Qualitative Research Approaches - Suryani, Anne (Jurnal ILMU KOMUNIKASI, 2008)
Abstract: This article reviews several differences between case study and ethnography in terms of definitions, characteristics, strengths and limitations. It provides current information by comparing these approaches from various social researchers’ perspectives. Although each method has strong points, they both have differences in conducting observation and interview as data collection techniques; choosing the length of time of data gathering and reporting details of a particular reality.